Long-term culture and characterization of patient-derived primary hepatocytes using conditional reprogramming. Issue 11 (August 2019) - Su, Shan; Di Poto, Cristina; Roy, Rabindra; Liu, Xuefeng; Cui, Wanxing; Kroemer, Alexander; Ressom, Habtom W
Cultivation of primary human hepatocytes (PHHs) often faces obstacles including failure of long-term in vitro culture, weak proliferation ability, rapid loss of liver-specific function and morphology, and tendency of fibrosis. Previous research focused on immortalization methods, such as telomerase and viral, to culture immortalized primary human hepatocytes, which may lose some of the normal properties. However, non-immortalized PHHs often fail to maintain long-term viability and functionality. These highlight the urgent need for developing new culture strategy for PHHs. In the present study, we isolated PHHs from fresh human liver tissues representing different liver diseases and age groups. We used conditional reprogramming, without permanent immortalization, for long-term in vitro primary human hepatocytes cultivation and characterization. For functional characterization, we assessed CYP3A4, 1A1 and 2C9 activities and measured the mRNA expression of albumin, s100a4, krt8, krt18, cyp1a1, cyp3a4, cyp2b6, cyp2c8, cyp2c9, and cyp2d6 . Additionally, we compared the DNA fingerprint of the cells against their original liver tissues using short tandem repeat (STR) analysis. We found that PHHs-derived from young patients can survive for more than three months, while the lifespan of primary human hepatocytes derived from adult patients ranges from two to three months, which is longer than most commercial primary hepatocytes. Importantly, the cells at early passages retain strong CYP3A4, 1A1 and 2C9 activities and the DNA fingerprints are identical with their original tissues. Through conditional programming, we achieved, for the first time, a high level of success rate in the long-term in vitro cultivation of primary human hepatocytes-derived patients representing diverse liver disease. Moreover, the conditional programming cell culture technology reported in this paper requires neither co-culture with additive cells, nor complex and expensive components, such as collagen sandwich or spheroid culture. We thus believe that the patient-derived PHHs cultivation using conditional programming may provide a viable and valuable cell model to study liver disease-related mechanisms. Impact statement: Commercially available primary human hepatocytes rapidly lose their proliferative ability and liver-specific functions over a few cultivation days. The demand for pharmaceutical toxicity screening and liver disease research requires the development of long-term primary hepatocyte culture methods. This manuscript addresses this challenge by introducing for the first time successful long-term in vitro cultivation of primary human hepatocytes from a range of liver transplantation patients using conditional reprogramming technique. The beauty of this technique is that it is not a permanent immortalization and does not require co-culture with additive cells. The primary human hepatocytes retain proliferative capacity, genetic stability, and hepatocyte-specific functions at early passages. In view of these, we believe that scientists and researchers will benefit from using these highly valuable cell models to study diverse liver diseases.